A Test of the Market Efficiency of the Integrated Latin American Market (MILA) Index in Relation to Changes in the Price of Oil - Hernández-Gamarra, Katerin; Sarmiento-Sabogal, Julio; Cayon-Fallon, Edgardo (International Journal of Energy Economics and Policy, 2015)
The purpose of this paper is to study if there is a Granger causality relationship between the price of oil and the prices of the stocks that compose the Integrated Latin American Market (MILA) Index. Our analysis found that from the perspective of the efficient market hypothesis (EMH), there is no empirical evidence that there is a Granger causality relationship between the price of oil and other commodities and the stocks that compose the MILA Index. Therefore, it is possible to conclude that based on the evidence, it is not possible to create an arbitrage strategy based on the price of oil and copper to achieve abnormal returns in the MILA Stock Market. In order to test for the Granger causality between the underlying variables, we used a leveraged bootstrap test developed by Hatemi-J (2012). Keywords: Market efficiency; asymmetric Granger causality; asset-pricing models; MILA Index; oil prices. JEL Classifications: G14; G15